A Review of immigration obstacles to PON-FTTH and its evolution around the world - Mustafa H. Ali; Hazim M. ALkargole; Tariq A. Hassan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The require a bandwidth of every person will be increased from 16 Mbit/s to 50 up to 100M bit/s in the next 5 years in most of the growing counties. To solve this problem, FTTH may be the appropriate solution in a wide range. We experimentally investigate the deploy of PON-FTTH based on different kinds of passive optical network technology (E-PON, G-PON and VCSEL) and study the Obstacles of PON-FTTH Immigration after comparing it with older service (XDSL). Then analysis the reason on why these technologies chose by some country not others and why the technological need in Europe different with need in Africa and America. We discussed the solutions in telecommunications networks and or the economic aspect of projects all over the world, we found that GPON is more appropriable for accomplishment PON-FTTH than other networks. Thus GPON has been chosen for Europe, America and middle east. Choosing GPON techniques is decided by many factors include the infrastructure that was made before, the people demand for service and how much service they need because the need in Europe different with need in Africa and American and so on. Finally, we will suggest the appropriate solution in the energy savings, cost effective, higher security, and side of service transparency over other access networks for the future demand.